Ship Iceberg Collision Database operations manual ... - Hill, B. (National Research Council of Canada. Institute for Ocean Technology, 2004)
The manual describes how to use the Ship Iceberg Collision Database developed by the Institute and available as a CD or on-line from the web site. ...